The effect of lubricant viscosity in cold forward plane strain extrusion test - Samion, Syahrullail (EuroJournals Publishing, Inc, 2009)
The effect of lubricant with three different viscosities was investigated by plane strain extrusion experiments and visioplasticity analyses. The lubricant is additive free paraffinic mineral oil. VG30 is a low viscosity lubricant with kinematic viscosity of 32 mm 2 /s at 40ºC. VG95 is a medium viscosity with kinematic viscosity of 92 mm 2 /s at 40ºC. VG460 is a high viscosity with kinematic viscosity of 462 mm 2 /s at 40ºC. The experiment used a cold work plane strain extrusion apparatus consist of a pair of taper die and a symmetrical workpiece (billet). The billet material was annealed pure aluminum A1100. The experiments were conducted at room temperature. The experimental results are focusing on the extrusion load, billet surface roughness, billet surface and grid pattern observation. The distribution of velocities and effective strain on the sliding plane of taper die were analyzed quantitatively, by using the visioplasticity method. From the results, low viscosity lubricant would give high extrusion load, however, low viscosity lubricant could produce product surface with low surface roughness